Early Detection and Prevention of Lungs Cancer using Artificial Neural Network - Supriya Narad; Dr. K. T. V. Reddy (International Journal of Engineering and Management Research, 2022)
Out of the dangerous diseases, cancer being one of the cause of death and it can be avoided if correctly detected in the early stage. The possibilities of survival will be increased if predicted and cured at early stage. To predict accurately and to provide best diagnosis, many mechanisms are developed in the field of Artificial Intelligence and machine learning. This paper provides a systematic review of different machine learning algorithms like Artificial Neural Network (ANN), Decision Trees (DT), Support Vector Machine (SVM), Random Forest (RF), Voting Classifier and Bayesian Network (BN). Survey also shows that ANN and SVM are preferred by researchers to develop the predictive models.